2017
DOI: 10.3389/fphar.2017.00222
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin Inhibits Store-Operated Ca2+ Entry and Alleviates Cardiac Hypertrophy

Abstract: Cardiac hypertrophy is a major risk factor for heart failure, which are among the leading causes of human death. Gastrodin is a small molecule that has been used clinically to treat neurological and vascular diseases for many years without safety issues. In the present study, we examined protective effect of gastrodin against cardiac hypertrophy and explored the underlying mechanism. Phenylephrine and angiotensin II were used to induce cardiac hypertrophy in a mouse model and a cultured cardiomyocyte model. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…; Zheng et al. ), downregulation of SOCE response as seen in direct co‐culture suggests that direct interaction with macrophages could play a role in preventing the development of hypertrophy in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 98%
“…; Zheng et al. ), downregulation of SOCE response as seen in direct co‐culture suggests that direct interaction with macrophages could play a role in preventing the development of hypertrophy in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Gastrodin (p-hydroxymethylphenyl-b-D-glucopyranoside) is the main bioactive ingredient of herbal Chinese medicine Gastrodia elata. It is clinically used to treat neurological and cardiovascular diseases, such as cardiac hypertrophy, hypertension, migraine, convulsions, dementia, and epilepsy [7,8]. The mechanism underlying the effects of gastrodin on the nervous and vascular system may be related to gamma-aminobutyric acid, glutamate, and calcitonin gene-related peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of STIM-1 resulted in hypertrophic arterial remodeling and cardiac hypertrophy in chronic ethanol-induced hypertensive rats [26]. For example, gastrodin, an agent used to treat hypertension, was found to suppress SOCE by reducing the expression of STIM-1 in a phenyl-ephrine-induced mouse model of cardiac hypertrophy [27]. Studies have also reported that SOCE plays a significant role in vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%